Cover Feature: Phosphonium‐Ring‐Fused Bicyclic Metallafuran Complexes of Ruthenium and Osmium (Chem. Eur. J. 39/2019). Issue 39 (6th June 2019) - Yeung, Chi‐Fung; Chung, Lai‐Hon; Ng, Sze‐Wing; Shek, Hau‐Lam; Tse, Sheung‐Ying; Chan, Siu‐Chung; Tse, Man‐Kit; Yiu, Shek‐Man; Wong, Chun‐Yuen
Abstract : Reactions between terminal ynones and ruthenium(II)/osmium(II) precursors with a 1, 1‐bis(diphenylphosphino)methane (dppm) auxiliary ligand produced metallafuran complexes with a fused five‐membered phosphonium ring. Kung Fu (literally means hard work in Cantonese) was spent on understanding their formation mechanism. These phosphonium‐containing metallafurans, like many phosphonium‐functionalized drugs, have the ability to induce mitochondrial dysfunction. They also exhibit stronger cytotoxicity against several human cancer cell lines in comparison with their metal precursors and the classic anticancer drug cisplatin. More information can be found in the Communication by C.‐Y. Wong et al. on page 9159 .